Uncertainty and Unemployment : The Effects of Aggregate and Sectoral Channels - Choi, Sangyup (IMF Working Papers; Working Paper ;, 2015)
We study the role of uncertainty shocks in explaining unemployment dynamics, separating out the role of aggregate and sectoral channels. Using S and P500 data from the first quarter of 1957 to third quarter of 2014, we construct separate indices to measure aggregate and sectoral uncertainty and compare their effects on the unemployment rate in a standard macroeconomic vector autoregressive (VAR) model. We find that aggregate uncertainty leads to an immediate increase in unemployment, with the impact dissipating within a year. In contrast, sectoral uncertainty has a long-lived impact on unemployment, with the peak impact occurring after two years. The results are consistent with a view that the impact of aggregate uncertainty occurs through a 'wait-and-see' mechanism while increased sectoral uncertainty raises unemployment by requiring greater reallocation across sectors.